2010
DOI: 10.1113/expphysiol.2010.053355
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Physiology –Research Paper: Modulation of N‐type calcium currents by presynaptic imidazoline receptor activation in rat superior cervical ganglion neurons

Abstract: Presynaptic imidazoline receptors (R i-pre ) are found in the sympathetic axon terminals of animal and human cardiovascular systems, and they regulate blood pressure by modulating the release of peripheral noradrenaline (NA). The cellular mechanism of R i-pre -induced inhibition of NA release is unknown. We, therefore, investigated the effect of R i-pre activation on voltage-dependent Ca 2+ channels in rat superior cervical ganglion (SCG) neurons, using the conventional whole-cell patch-clamp method. Cirazolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Dong et al, 2009;Lai et al, 2014). Previous studies have reported reduced Ca 2+ -influx through reversible blockade of NMDARs and N-type Ca 2+ currents after I 2 -or I 1 -IR ligands, respectively (Chung et al, 2010;Han et al, 2013;Jiang et al, 2010;Kim et al, 2011;Olmos, DeGregorio-Rocasolano, et al, 1999;Olmos, Ribera, et al, 1996; see Figure 6). Thus, in agreement with a recent report (Jiang et al, 2010), the inhibitory effects of IR drugs on calpain activity (reduced fragmentation of spectrin α and p35) appear to result from decreased intracellular Ca 2+ concentrations and not from direct enzyme inhibition.…”
Section: Discussionmentioning
confidence: 87%
“…Dong et al, 2009;Lai et al, 2014). Previous studies have reported reduced Ca 2+ -influx through reversible blockade of NMDARs and N-type Ca 2+ currents after I 2 -or I 1 -IR ligands, respectively (Chung et al, 2010;Han et al, 2013;Jiang et al, 2010;Kim et al, 2011;Olmos, DeGregorio-Rocasolano, et al, 1999;Olmos, Ribera, et al, 1996; see Figure 6). Thus, in agreement with a recent report (Jiang et al, 2010), the inhibitory effects of IR drugs on calpain activity (reduced fragmentation of spectrin α and p35) appear to result from decreased intracellular Ca 2+ concentrations and not from direct enzyme inhibition.…”
Section: Discussionmentioning
confidence: 87%
“…The amplitude of the cirazoline-dependent hyperpolarization in the presence of an α 1 -adrenergic receptor blocker prazosin in the bath (100 μM, Kobayashi, 2007 ; Luo et al, 2014 , Figures 3Ca,b ) was not significantly different than that in the presence of cirazoline alone (-4.4 ± 0.5 mV, n = 6, p = 0.2344, unpaired t -test). Cirazoline can activate imidazoline receptors ( Chung et al, 2010 ). Therefore, the effect of cirazoline on the membrane potential was tested in the presence of an imidazoline receptor antagonist efaroxan (100 μM).…”
Section: Resultsmentioning
confidence: 99%
“…channels is unclear, it is known that voltage-dependent Ca 2? channels are inhibited by imidazoline receptor activation in rat cervical ganglion neurons or hippocampal neurons [48,49]. Thus, it is possible that the inhibitory effects of a 2 -agonists and a 2 -antagonists that contain an imidazole ring on Na ?…”
Section: Discussionmentioning
confidence: 99%